Structural basis of drugs that increase cardiac inward rectifier Kir2.1 currents. (1st November 2014) - Gómez, Ricardo; Caballero, Ricardo; Barana, Adriana; Amorós, Irene; De Palm, Sue-Haida; Matamoros, Marcos; Núñez, Mercedes; Pérez-Hernández, Marta; Iriepa, Isabel; Tamargo, Juan; Delpón, Eva
Abstract: Aims: We hypothesize that some drugs, besides flecainide, increase the inward rectifier current ( I K1 ) generated by Kir2.1 homotetramers ( I Kir2.1 ) and thus, exhibit pro- and/or antiarrhythmic effects particularly at the ventricular level. To test this hypothesis, we analysed the effects of propafenone, atenolol, dronedarone, and timolol on Kir2.x channels. Methods and results: Currents were recorded with the patch-clamp technique using whole-cell, inside-out, and cell-attached configurations. Propafenone (0.1 nM–1 µM) did not modify either I K1 recorded in human right atrial myocytes or the current generated by homo- or heterotetramers of Kir2.2 and 2.3 channels recorded in transiently transfected Chinese hamster ovary cells. On the other hand, propafenone increased I Kir2.1 (EC50 = 12.0 ± 3.0 nM) as a consequence of its interaction with Cys311, an effect which decreased inward rectification of the current. Propafenone significantly increased mean open time and opening frequency at all the voltages tested, resulting in a significant increase of the mean open probability of the channel. Timolol, which interacted with Cys311, was also able to increase I Kir2.1 . On the contrary, neither atenolol nor dronedarone modified I Kir2.1 . Molecular modelling of the Kir2.1–drugs interaction allowed identification of the pharmacophore of drugs that increase I Kir2.1 . Conclusions: Kir2.1 channels exhibit a binding site determined by Cys311 that is responsible for drug-induced I Kir2.1 increase. Drug binding decreases channel affinity for polyamines and current rectification, and can be a mechanism of drug-induced pro- and antiarrhythmic effects not considered until now.